2016
DOI: 10.7567/jjap.55.05fj13
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructure optimization for increasing LED efficiency

Abstract: Computer simulations were performed to increase the quantum efficiency of LED by optimizing the nanoheterostructure (NH). Furthermore, the InGaN and AlGaP NHs for LEDs were optimized. On the basis of the optimum NH, ways to further increase the efficiency and the influence of impurities and indium atoms doped into barriers between quantum wells were investigated. The optimum impurity and indium atom concentrations to achieve higher flux were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…SimWindows software (SW) was used in current investigation [6]. Main features of the software and method of its usage for semiconductor devices simulation have been described in [2][3][4][5][6][7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SimWindows software (SW) was used in current investigation [6]. Main features of the software and method of its usage for semiconductor devices simulation have been described in [2][3][4][5][6][7].…”
Section: Methodsmentioning
confidence: 99%
“…Our investigations based on computer simulation showed that, based on such heterostructures not only photodiodes can be produced but also phototransistors (PT) with a sensitivity of more than 100 A/cm 2 , in this wavelengths area [2][3][4][5][6][7]. It has been proposed ultraviolet phototransistor (UV PT) structure, based on the capabilities of this technology with GaN and AlGaN collector.…”
Section: Introductionmentioning
confidence: 99%
“…structures. The average size of ferromagnetic MnSb clusters in granular structures was 24 nm [36][37][38][39][40]. Fig.…”
Section: Spintronicsmentioning
confidence: 94%
“…Our investigations based on computer simulation showed that, based on such NH, not only photodiodes but also phototransistors (PT) with a sensitivity of more than 100 A/cm 2 can be produced, in this wavelengths area [35][36][37][38][39][40][41][42][43]. Ultraviolet phototransistor (UV PT) structure has been proposed, based on the capabilities of this technology with GaN and AlGaN collector.…”
Section: Photodetector (Phototransistor) Improvementsmentioning
confidence: 99%